Between Gift and Profit: Appropriative Practices as a New Approach to Digital Economy Analysis - Denisova, Maria (Journal of Economic Sociology, 2020)
The author of the book sets the non-trivial task of developing an approach to the economic analysis that would include the diversity of economic practices and at the same time indicate the recipients of benefits. In criticizing the ideas of Marxists and mainstream economists, the author concludes that they are unable to see economies beyond capitalism and market relations, which automatically excludes gifts and hybrid economic forms from any economic analysis. Five case studies from the digital economy of Apple, Wikipedia, Google, YouTube and Facebook demonstrate the analytical potential of a new approach—the political economy of practices, which considers the diversity of economic practices. By putting emphasis on various combinations of appropriating practices, the author demonstrates the success of the enterprises in the digital economy, which cannot be explained by perfect competition or the exploitation of wage labor. This book is an excellent example of the substantive approach to economic analysis and would be especially interesting to those who are interested in the coexistence of market and non-market economic forms, particularly in the digital world.